Parenting Patterns' Impact on the Likelihood of Mental Disorders in Palembang, Indonesia - Hidayat, Rachmat (Scientia Psychiatrica, 2024)
Introduction: Parenting style has a crucial role in shaping a child's physical and mental growth. The objective of this study is to assess the impact of parenting styles on the likelihood of developing mental problems in the urban area of Palembang, Indonesia. Methods: This study employed a cross-sectional research methodology, encompassing a sample of 1,000 participants aged between 18 and 65 years. We categorized the participants based on the type of parenting style they experienced, namely authoritative, permissive, and authoritarian parenting. We used the Kessler Psychological Distress Scale (K10) questionnaire to assess the likelihood of mental illnesses. Results: The study found that individuals raised with an authoritative parenting style had a lower vulnerability to mental problems compared to those raised with either a permissive or authoritarian parenting style. Conclusion: The practice of authoritative parenting can serve as a safeguard against susceptibility to mental diseases.